MSC virtual e-abstract (CPP-03) - Stroke Conference 2020, Malaysia (Journal Of Cardiovascular, Neurovascular & Stroke, 2020)
Activation of stroke protocol and thrombolysis in non ct hospital. Outcome of stroke thrombolysis in lacunar stroke at HSNZ. The use of international classification of functioning, disability and health (icf) to identify. Cerebral venous sinus thrombosis: Clinical features and rehabilitation outcome. Unlocking the locked-in syndrome (lis)’: International classification of functioning, disability and health (icf) as a clinical tool in formulating rehabilitation plans and overcoming challenges in lis patients. Vestibular migraine : A case report. Burden of stroke in Hospital USM, Kota Bharu, Malaysia.